Participation in Local Elections: 'Why Don't Immigrants Vote More?'. Issue 2 (10th July 2017) - Ruedin, Didier
Abstract: Why do immigrants vote less in local elections when they have the right to vote? I present a new representative survey on participation in the 2015 municipal elections in the Canton of Geneva, Switzerland, and predict electoral participation with logistic regression models. Most immigrant groups vote less than the majority population. Four explanations are tested for this difference: social origin (resources), political engagement, civic integration and networks, as well as socialisation. Individually, all these explanations are associated with differences in electoral participation, but contrary to some recent studies, substantive differences between nationalities remain.